2018
DOI: 10.1177/1550059418800889
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effect of Multisession Transcranial Direct Current Stimulation on Cognition in Dementia and Mild Cognitive Impairment

Abstract: There have been increasing efforts to investigate the effects of neuromodulation techniques, such as transcranial direct current stimulation (tDCS), on cognitive impairment in dementia and related conditions. In this systematic review and meta-analysis, we assessed the efficacy of multisession anodal tDCS compared with sham stimulation for improving global cognition and specific cognitive domains in both Alzheimer's disease and mild cognitive impairment. Eight articles meeting the criteria for inclusion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 51 publications
0
34
0
1
Order By: Relevance
“…These techniques provide promising and multiple beneficial opportunities in neurologic and psychiatric diseases (Fregni et al, 2006a; Knöchel et al, 2012; Kuo et al, 2014; Forbes et al, 2015) and also in health (Choe et al, 2016; Ward et al, 2017). More specifically, there is increasing evidence from clinical trials that both tDCS and AE can be beneficial in stroke (Duncan et al, 2003; Fregni et al, 2005; Tang et al, 2009; Brunoni et al, 2012; Marquez et al, 2015), fibromyalgia (Castillo-Saavedra et al, 2016; Fink and Lewis, 2017), Alzheimer’s disease (Ferrucci et al, 2008; Intlekofer and Cotman, 2013; Farina et al, 2014; Hsu et al, 2015; Inagawa et al, 2018), Parkinson’s disease (Fregni et al, 2006c; Schenkman et al, 2012), major depressive disorder (Fregni et al, 2006b; Kuo et al, 2014; Schuch et al, 2016; Yokoi et al, 2018), and schizophrenia treatments (Gorczynski and Faulkner, 2010; Kuo et al, 2014; Smith et al, 2015; Yokoi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques provide promising and multiple beneficial opportunities in neurologic and psychiatric diseases (Fregni et al, 2006a; Knöchel et al, 2012; Kuo et al, 2014; Forbes et al, 2015) and also in health (Choe et al, 2016; Ward et al, 2017). More specifically, there is increasing evidence from clinical trials that both tDCS and AE can be beneficial in stroke (Duncan et al, 2003; Fregni et al, 2005; Tang et al, 2009; Brunoni et al, 2012; Marquez et al, 2015), fibromyalgia (Castillo-Saavedra et al, 2016; Fink and Lewis, 2017), Alzheimer’s disease (Ferrucci et al, 2008; Intlekofer and Cotman, 2013; Farina et al, 2014; Hsu et al, 2015; Inagawa et al, 2018), Parkinson’s disease (Fregni et al, 2006c; Schenkman et al, 2012), major depressive disorder (Fregni et al, 2006b; Kuo et al, 2014; Schuch et al, 2016; Yokoi et al, 2018), and schizophrenia treatments (Gorczynski and Faulkner, 2010; Kuo et al, 2014; Smith et al, 2015; Yokoi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, many previous studies did not provide sample size calculations and, thus, the results from these studies may be false-negatives, when the results are actually positive. Further, according to our meta-analytic review (Inagawa et al, 2018), the quality of study designs in these previous studies seems to be poor. In fact, many of them did not clearly state allocation concealment, blinding of personnel, or any method of handling missing data.…”
Section: Introductionmentioning
confidence: 94%
“…A recent meta-analysis of randomized controlled trials indicated that tDCS may be effective on cognition in healthy participants (Dedoncker et al, 2016); however, a meta-analysis of randomized controlled trials on the effect of tDCS on cognition in patients with dementia and MCI shows that tDCS is not always effective overall (Inagawa et al, 2018). The discord among the findings of these studies may be due to differences in the electrode montage, stimulation parameters, and timing of tDCS in the training tasks (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) are two forms of noninvasive brain stimulation (NIBS) that are showing promise as potential treatments for AD and related conditions. Although there are several excellent reviews on NIBS and AD, this scoping review focuses on the randomized controlled trials (RCTs) that tested rTMS and tDCS in AD and mild cognitive impairment (MCI) and highlights for future studies some considerations related to mechanistic targets and methodological parameters.…”
mentioning
confidence: 99%